Evaluation of Qatari and Canadian Pharmacy Students Learning Together about Cultural Competency using Videoconference Educational Activities - Derek Jorgenson; Kyle J Wilby; Jeff Taylor (University of Minnesota Libraries Publishing, 2016)
Background: Pharmacists are under pressure to provide patient centered care within increasingly culturally diverse settings. Pharmacy schools play an important role in educating learners regarding culture and its impact on patient care. Objectives: The objectives of this study were to determine if a novel cultural competency learning activity, which involved students from two culturally and ethnically different pharmacy schools learning together using videoconference education activities, improved: (1) student knowledge and confidence pertaining to cultural competency concepts, (2) attitudes and perceptions towards being a culturally competent pharmacist, and (3) academic performance related to cultural competency case studies. Methods: Pharmacy students from Qatar University in Doha, Qatar (n=25) and the University of Saskatchewan in Saskatoon, Canada (n=85) participated in a cultural competency activity comprised of small group work on a patient case study, followed by tutorial discussions. Some Canadian students (n=31/85) worked collaboratively (via video conference) with the students from Qatar. The evaluation used a convergent mixed methods design comprised of: (1) a pre and post session survey measuring student knowledge and confidence; (2) pre and post session student self-reflections; and, (3) student academic performance on care plans and an observed structured clinical exam (OSCE). Results: The survey identified small but statistically significant (p<0.05) improvements in knowledge and confidence with respect to 11 of the 12 questionnaire items in the students from Canada and 2 of the 12 items in the students from Qatar. The self-reflections found that 44.4% (n=36/81) of students who completed the pre and post reflective questions reported a change in knowledge and attitudes regarding cultural competency, but a reason for the change was not evident. Student grades on the cultural competency care plans and the OSCE were not different between the students who worked collaboratively across the two schools compared with those who did not. Conclusion: The cultural competency student activity showed small improvements in pharmacy student knowledge, attitudes and confidence, but did not affect academic performance. Future research in this area could utilize a greater diversity of methodological approaches, including a focus on student self-reflection and qualitative assessment, to better capture student competency.   Type: Original Research